Conservation planning for pollinators in the U.S. Great Plains: considerations of context, treatments, and scale. Issue 7 (5th July 2021) - Niemuth, Neal D.; Wangler, Brian; LeBrun, Jaymi J.; Dewald, David; Larson, Scott; Schwagler, Todd; Bradbury, Curtis W.; Pritchert, Ronald D.; Iovanna, Rich
Abstract: Populations of many species of grassland‐associated butterflies, moths, and bumblebees in the Great Plains of North America are experiencing steep declines due to habitat loss and degradation—primarily conversion of grasslands to row‐crop agriculture and invasion of woody plants and exotic cool‐season grasses—and insecticide use. These declines are exacerbated by the generally limited dispersal ability of insects, which make local populations susceptible to extirpation following habitat fragmentation. Interest in pollinator conservation has grown substantially in recent years, but information to guide pollinator conservation across the region is limited. We used pollinator biology along with principles of landscape ecology and metapopulation dynamics to develop a simple decision matrix based on patch size and inter‐patch distances to guide landscape‐scale grassland conservation efforts in the U.S. northern Great Plains. When applied to spatial land cover data depicting potential pollinator habitat, the matrix uses landscape characteristics to guide placement of conservation treatments to help ensure persistence of target pollinator populations. Patch size and connectivity thresholds can be set to match characteristics of target species, but in all cases, local management will be necessary to ensure that fine‐grained features such as nectar sources and host plants are present. Applying the matrix to habitat layers for a nine‐state analysis region showed substantial geographic variation in conservation needs, opportunities, and potential treatments. We also demonstrate that non‐native planted cover such as alfalfa and certain grasslands enrolled in the Conservation Reserve Program can substantially enhance landscape structure by increasing grassland patch size and core area while decreasing distance between patches. Pollinators dependent on native prairie will also benefit from planted cover that provides nectar sources and serves as a buffer from pesticides associated with croplands. Consistent with the principles of strategic habitat conservation, targeted monitoring and research will be necessary to validate and adapt the model to meet local conditions.